2008
DOI: 10.1364/josab.25.000463
|View full text |Cite
|
Sign up to set email alerts
|

Optical parametric amplifiers using chirped quasi-phase-matching gratings I: practical design formulas

Abstract: Optical parametric amplifiers using chirped quasi-phase-matching (QPM) gratings offer the possibility of engineering the gain and group delay spectra. We give practical formulas for the design of such amplifiers. We consider linearly chirped QPM gratings providing constant gain over a broad bandwidth, sinusoidally modulated profiles for selective frequency amplification and a pair of QPM gratings working in tandem to ensure constant gain and constant group delay at the same time across the spectrum. The analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
133
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(138 citation statements)
references
References 38 publications
3
133
0
Order By: Relevance
“…The broad bandwidth response is in particular importance for frequency conversion of ultrashort pulses. Chirped QPM gratings have been utilized to manipulate short pulses both in second harmonic generation (SHG) [9,10,11], difference frequency generation (DFG) [12], and in parametric amplification [10,13]. Recent application showed that by using a disordered material (random QPM), an extreme broad bandwidth was obtained, although at a price of severe reduction of the conversion efficiencies [14].…”
mentioning
confidence: 99%
“…The broad bandwidth response is in particular importance for frequency conversion of ultrashort pulses. Chirped QPM gratings have been utilized to manipulate short pulses both in second harmonic generation (SHG) [9,10,11], difference frequency generation (DFG) [12], and in parametric amplification [10,13]. Recent application showed that by using a disordered material (random QPM), an extreme broad bandwidth was obtained, although at a price of severe reduction of the conversion efficiencies [14].…”
mentioning
confidence: 99%
“…Our results also demonstrate that this technique can be combined with APPLN amplifiers in a practical "hybrid" OPCPA system configuration. Furthermore, we showed in section 5.1 how the combination of non-collinear beam geometry and chirped QPM devices enables octave-spanning amplification; the use of nonlinear chirp profiles would even enable customizable gain profiles across this amplification bandwidth [30,35]. This approach, together with further power scaling achievable by the use of wide-aperture QPM devices as the gain medium [36], thus provides a route to amplification of high-energy single-cycle pulses.…”
Section: Discussionmentioning
confidence: 92%
“…(3). Noting that the small-gain is given, for a linearly chirped QPM grating, by G ss =exp(2πΛ) [30], where Λ=γ 2 /|Δk'| and Δk'=d(Δk)/dz=-dK g /dz is the QPM chirp rate, we arrive at the following:…”
Section: Aperiodic Qpm Devicesmentioning
confidence: 99%
“…(3) as a sum of the contributions from the relevant QPM orders, whose individual Fourier spectra may have simple closed-form solutions. For example, these individual Fourier spectra correspond to sinc functions for periodic gratings, and to error functions for linearly chirped gratings [31,34]. Writing g z z from Eq.…”
Section: B Ensemble-averaged Noise Pedestal and Efficiency Reductionmentioning
confidence: 99%